DESIGN & DEVELOPMENT OF PORTABLE MILLING MACHINE - Manjunatha C J; Manjunath K; Suresha P (International Journal of Innovations in Engineering Research and Technology, 2021)
Increase in the rapid growth of Technology significantly increased the usage and utilization of CNC systems in industries but at considerable expensive. The idea on fabrication of low cost CNC Milling Machine came forward to reduce the cost and complexity in CNC systems. This paper discusses the development of a low cost CNC Milling Machine which is capable of 3-axis simultaneous interpolated operation. The lower cost is achieved by incorporating the features of a standard PC interface with micro-controller based CNC system in an Arduino based embedded system. The system also features an offline G-Code parser and then interpreted on the micro-controller from a USB.